Perubahan Sistem Pelayanan Makanan pada Usaha Kuliner Selama Masa Pandemi COVID-19 dan Era Kebiasaan Baru di Kota Makassar - Nurbaya Nurbaya; Wahyu Chandra; Ansar Ansar (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Food safety is one of the people's concerns in buying and consuming food during the Covid-19 pandemic. This requires culinary entrepreneurs to meet food safety standards in the food processing system. This study aims to determine the food service system carried out by culinary entrepreneurs during the Covid-19 pandemic and in the era of new normal in Makassar City. With a qualitative approach, 33 informants were selected purposively to be involved in this study which was distributed into 17 in-depth interviews and 3 FGDs. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion or verification. This research found that culinary entrepreneurs applied health standards in their restaurants by providing handwashing facilities, barrier plastic, keeping tables/chairs apart, and requiring consumers to wear masks. Food processing requires food processors to use disposable plastic gloves and masks as well as tighter food packaging. It is concluded that culinary entrepreneurs have implemented safety and health standards in the food service system both in food processing and food packaging. It is highly recommended that culinary entrepreneurs perform routine cleaning and disinfecting at their restaurants so that efforts to prevent Covid-19 can be maximized, especially in the culinary business sector.